1973
DOI: 10.1111/j.1744-7348.1973.tb07297.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in the intensity of diapause in winter eggs of fruit tree red spider mite, Panonychus ultni

Abstract: S U M M A R YWinter eggs of Panonychus ulmi from six orchards in Kent showed a range of 3 weeks in the dates of 50% hatch at field temperatures. From the effects of the duration and temperature of chilling, and the temperature of incubation, it was concluded that samples varied in their chilling requirement, and not in threshold temperatures for development. Diapause was terminated most effectively by chilling initially at o "C (for late-hatching strains) or so, followed by 9" for the last month or two. Herita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1976
1976
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…For example, Cranham (1972) showed egg hatching at -3 ºC and − 6 ºC; while Lees (1953) reported that no emergence occurred at -5 ºC. Cranham (1973) further attributed these results to intraspeci c variation and showed that six different populations collected at different sampling points in the southeast of England showed variable responses to temperature in relation to diapause termination. These results correlated well with eld observations because the populations that terminated diapause the earliest in the eld, were also breaking diapause earlier at the xed temperature of 0 ºC under laboratory conditions.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…For example, Cranham (1972) showed egg hatching at -3 ºC and − 6 ºC; while Lees (1953) reported that no emergence occurred at -5 ºC. Cranham (1973) further attributed these results to intraspeci c variation and showed that six different populations collected at different sampling points in the southeast of England showed variable responses to temperature in relation to diapause termination. These results correlated well with eld observations because the populations that terminated diapause the earliest in the eld, were also breaking diapause earlier at the xed temperature of 0 ºC under laboratory conditions.…”
Section: Discussionmentioning
confidence: 98%
“…This period was shorter than previously reported (Lees 1953; Koveos and Broufas 1999) that established a minimum of 40-50 days before diapause termination. These results may be explained by the different moment of collection of the eld populations used for the experiments because P. ulmi females can extend their period of oviposition over 6-8 weeks (Cranham 1973). This may translate into a different accumulation of temperature on overwintering eggs from early and late oviposition events; thereby in uencing all parameters under study, and confounding comparisons between locations and studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, chemical control can often disrupt key natural enemies in the crop (Easterbrook, 1997 a , b ); exploiting pest predators and parasitoids, by either habitat augmentation (Easterbrook & Tooley, ) or introductions (Easterbrook et al ., ; Fitzgerald et al ., , ) could mitigate the need for some pesticide applications. Studying the biology of pest species (Cranham, , ) and the parameters for reproduction and population build‐up, coupled with the development of techniques such as electrophoresis (Murray & Solomon, ; Fitzgerald et al ., ), monoclonal antibodies or molecular markers, has permitted an understanding of ‘who eats who’ and ultimately resulted in a reduced need for many broad spectrum chemical control measures. Utilising natural enemies is a free service which can keep pests in check (Campbell, ; Easterbrook, 1997 a , b ; Campbell & Lilley, ; Campbell & Cone, ).…”
Section: The Last Centurymentioning
confidence: 99%